Measurement of Usability Online Storage in Cloud Computing for University Users - I Wayan Yudha Saputra, Gilbert Watae, Nancy Runtukahu (International Journal of Information Technology and Education, 2021)
Cloud computing technology or often known as Cloud Computing is present as an impact of changes in the cultural environment and competitive ecosystem on Higher Education in the world, including Indonesia. Cloud computing is actually a combination of the use of computer technology ('computing') and Internet-based development ('cloud'). This research was conducted at Manado State University, the respondents themselves include lecturers and students. This study uses a use questionnaire that has aspects of effectiveness, efficiency and satisfaction. In collecting data the researchers used a questionnaire with the number in this study there were 21 respondents with 10 attributes of the questions asked. After collecting data, the analysis will be carried out using the Likert Scale method.